Attribute-based proxy signature scheme for unmanned aerial vehicle networks - Lei HE; Jianfeng MA; Dawei WEI (Tongxin xuebao)
It is necessary to use digital signature scheme to protect integrity and authentication of commands sent by command agencies to unmanned aerial vehicle (UAV) in the UAV networks.Moreover, the signature scheme should ensure UAV can receive signature in time and protect privacy of signers.Therefore, an attribute-based proxy signature scheme for UAV networks was proposed and its security was analyzed.The proposed signature scheme has existential unforgeability under selective-attribute and chosen message attacks, and privacy of signers is protected.Its efficiency was analyzed in terms of computation costs and communication costs, and compared with other related signature schemes.The results indicate the proposed signature scheme has less computation costs when its communication costs are at the same level with other signature schemes.